ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL OPERASI HITUNG BILANGAN CACAH - Yunni Arnidha, author (JURNAL E-DUMATH, 2015)
This study aims to determine the type of error that made the students in solving arithmetic operation of natural numbers in the form of addition and subtraction. This study was a descriptive one. The population in this study were all second grade students of SD Negeri 4 Podomoro which numbered 30 people. The samples used were all students of class II because the number of students is less than 100 people. Data collection techniques used in the form of a valid and reliable test. After the test is given, then the results of tests examined and analyzed to determine the type of error that made the students. The analysis showed that the mistakes made by students in solving arithmetic operation of natural numbers such as addition and subtraction . This type of error in the addition operation, the type of basic factual errors summation with a percentage of 35%, the type of random errors with a percentage of 10.02%. This type of error in calculating the reduction of operating natural numbers, that is kind of basic factual errors, with the percentage of 36.58% reduction. Types of random errors with the percentage of 18.40%.Keywords: Error Analysis, Numbers Count, Operation of Addition and Subtraction